2017
DOI: 10.1159/000479871
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age and Aerobic Exercise Training on Conduit Artery Wall Thickness: Role of the Shear Pattern

Abstract: Hemodynamic shear stress is the frictional force of blood on the arterial wall. The shear pattern in the conduit artery affects the endothelium and may participate in the development and progression of atherosclerosis. We investigated the role of the shear pattern in age- and aerobic exercise-induced changes in conduit artery wall thickness via cross-sectional and interventional studies. In a cross-sectional study, we found that brachial shear rate patterns and brachial artery intima-media thickness (IMT) corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
2
0
1
Order By: Relevance
“…Lower brachial retrograde and oscillatory shear were consistent with results of previous interventional studies 20,21) demonstrating that short-term aerobic exercise training reduces brachial artery retrograde shear. On the other hand, Casey et al 9) reported that endurance exercise-trained older adults have lower retrograde and oscillatory shear in the common femoral artery; whereas they could not observe significant differences in the brachial artery between the endurance-trained individuals and their sedentary counterparts, though the endurancetrained had relatively lower retrograde and oscillatory shear.…”
Section: Discussionsupporting
confidence: 90%
“…Lower brachial retrograde and oscillatory shear were consistent with results of previous interventional studies 20,21) demonstrating that short-term aerobic exercise training reduces brachial artery retrograde shear. On the other hand, Casey et al 9) reported that endurance exercise-trained older adults have lower retrograde and oscillatory shear in the common femoral artery; whereas they could not observe significant differences in the brachial artery between the endurance-trained individuals and their sedentary counterparts, though the endurancetrained had relatively lower retrograde and oscillatory shear.…”
Section: Discussionsupporting
confidence: 90%
“…Aerobic training promotes vascular adaptations in the conductance arteries (with decreased arterial stiffness and improved endothelial function), arterioles (by decreasing the vessel wall-to-lumen ratio), and capillaries, stimulating angiogenesis. 99,100 Thus, physical exercise has multifactorial effects on HTN, and is considered a key intervention to mitigate the burden of the disease and its comorbidities. 101 The antihypertensive effect of exercise is comparable to that of medication, 102 and both can be additive, occasionally requiring adjustments of drug dosage.…”
Section: Therapeutic Benefits Of Physical Exercisementioning
confidence: 99%
“…[ 47 , 48 ]. Tanahash et al [ 49 ] conducted 12 weeks of aerobic training in 102 adults and found that the brachial artery WSS increased after intervention. Green et al [ 21 , 23 ] recently demonstrated that artery function changed immediately during acute exercise by the stimulation of hemodynamic factors, whereas chronic functional adaption was probably induced by repeatedly being exposed to episodic bouts of such stimuli.…”
Section: Discussionmentioning
confidence: 99%